Mental health and Canadian society : historical perspectives - Wright, David, 1965-; Moran, James E. (McGill-Queen's/Associated Medical Services studies in the history of medicine, health, and society, 2006)
"In 1860, inmates built a brick wall around the Toronto Lunatic Asylum to separate themselves from prying eyes. The lunatic asylum has played a continuing role in historical attempts to deal with mental health, injecting tragic, almost gothic overtones of geographical isolation, medical experimentation, and social control into public perceptions of the field. In Mental Health and Canadian Society leading researchers challenge generalisations about the mentally ill and the history of mental health in Canada. Considering the period from colonialism to the present, they examine such issues as the rise of the insanity plea, the Victorian asylum as a tourist attraction, the treatment of First Nations people in western mental hospitals, and post-World War II psychiatric research into LSD. Their original conclusions challenge us to rethink present mental health policies, which continue to be influenced by an imagined history of the lunatic asylum."--